Faith Schools and Society : Civilizing the Debate. - Cairns, Jo (Bloomsbury Publishing, 2009)
- Do faith schools have a place in a plural society? - Which types of school contribute most effectively to a plural society? This fascinating monograph seeks to answer these questions and more by exploring the fit between personal, spiritual and academic goals in contemporary educational experience and individual school cultures. Jo Cairns, a well-respected authority on faith schools, argues that educational ideology in plural societies has to find a way of recognizing and responding to the ''predicament'' of pluralism as it is experienced by individuals and communities. This provocative and.